Design Improvement of a Helicopter Tail Reducer Casing - Guo Tiancai; Mei Qing; Xue Tongbo; Huang Zhenrong (Jixie chuandong)
The helicopter tail reducer casing often fail in the process of development. A design improvement scheme of a helicopter tail reducer casing is proposed based on the test results of the applied full stress monitoring method. The full stress monitoring method contains static test,fatigue test,ground test and flight test. The static and fatigue weak position of the casing is exposed by the static test and fatigue test. Through the ground test and the flight test,it is found that the main cause of failure is the resonance between the casing and system. According to the above test results,the design improvement scheme is proposed. The main contents are as follows,changing the connecting strength of the reinforcing plate of the foot,reducing the thickness of the lightening hole in the ribbed plate area,increasing the thickness of the install foot,increasing the thickness of install side of the pinion roller bearing. The above local changes make the casing well matched with the system,meanwhile the stress is redistributed to improve its fatigue and static property. The dynamic stress level of the casing is reduced by 49%after improvement. The quality is significant increased by the ground test and the flight test.